Rekayasa Sistem Informasi Kesehatan Dan Informasi Asupan Kalori(Gizi) Bagi Ibu Hamil - Idayani, Mei, Hernawan Sulistyanto, S.T.,M.T (2016)
Pregnancy is something that is desirable, because this is the beginning to be a mother. Besides preparing baby gear, the more important is the prospective mother should give greater attention to matters relating to the growth and development of the baby. Good or less good development of the child will be affected by the entry of nutrients consumed by the pregnant mother. The process of pregnancy does not always run smoothly. Pregnancy could be experiencing interference, both in young pregnancy nor old enough. Pregnancy tests are absolutely necessary for every pregnant woman. The purpose of supervision and examination of pregnant women is to prepare physically and mentally, save the mother and her baby in the womb, childbirth and the postpartum period. The formulation of the problems that are the focus of this research is, how to build a system that can be used by pregnant women to count calorie intake (nutrition) based on weight, height, maternal age, gestational age and level of activity of mothers using formula Harris Benedict and plan a dinner menu and can help pregnant women to overcome minor problems regarding the health of the mother during pregnancy. For the tests conducted on 10 women who had never been pregnant and 10 pregnant women. Results obtained are 9 out of 10 women who had never been pregnant stated strongly agree that wesite like this is needed for alternative referral during pregnancy. 9 pregnant women agree that the website is worth a look, quite clear and easy to use. 7 pregnant women agree that this web-based health referral greatly assist the mother during pregnancy.